Comparison of shoulder kinematics and kinetics during running throws with whip-like and circular wind up in elite handball players - Van den Tillaar, R. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The purpose of the current study was to compare shoulder kinematics and kinetics between the whip-like and circular wind-ups in running throws in handball. Thirteen elite handball players performed running throws with a circular and whip-like wind up. The main findings were that peak ball velocity and maximal shoulder distraction force were higher with the circular wind up together with lower maximal external shoulder rotation angle and higher angular external rotation velocity compared with the whip-like wind up. It was concluded that the higher distraction force was due to the combination of higher maximal angular horizontal flexion and internal rotation at ball release. While no significant different torques were found between the two wind up, this was probably caused by the variability in throwing technique experience due to the different playing positions included in the present study.